Matrix Representations of Finite $p$-Groups over Commutative Local Rings of Characteristic $p^s$ - Gudivok, P. M.; Pogorilyak, E. Y. (Ukrains’kyi Matematychnyi Zhurnal, 2002)
We determine in what cases the problem of description of nonequivalent matrix representations of a finite $p$-group over a commutative local ring of characteristic $p^s$ is wild.